PERILAKU PENCARIAN PELAYANAN KESEHATAN DALAM KONSEP PERAWATAN MANDIRI TERKAIT HIV AIDS DAN IMS PADA KALANGAN LELAKI BERHUBUNGAN SEKS DENGAN LELAKI - Raya, Agus Jagat (Coping: Community of Publishing in Nursing; Vol 2 No 1 (2014): JURNAL EDISI JANUARI-APRIL 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE The transmission of HIV AIDS and STIs dominated through unprotected sexual intercourse. Men who have sex with men (MSM) have a high risk of contracting and transmitting HIV AIDS and STIs. Thus, it increases cases of HIV AIDS and STIs. Actions taken to care for themselves independently deemed not optimal without visiting and utilizing health services. This study aims at describing, exploring, and uncovering the health-seeking behavior on self care concept related HIV AIDS and STIs among MSM in the city of Denpasar. In addition, the driving and inhibiting factors MSM seek health care are analyzed. This study uses a qualitative design with a phenomenological approach. Participants are 7 people selected using purposive sampling methods and data collection techniques with in-depth interviews. Interviews were recorded and then analyzed using thematic analysis. Afterwards, the data and test of the data validity were analyzed. Results of this study indicate that the search behavior of MSM to health care services is quite good, merely it is required to give assistances for understanding and mentoring continually so that , the process in independently caring for themselves can be well understood . Views on health care by the MSM to be are quite good, including health workers, facilities, data storage, and the clinic. MSM motivating factor to seek health care are namely desire, awareness, and call a friend. The inhibiting factors are the lack of information, less activeness , difficulties in obtaining health care, no friends, cost, and fear of test results. One suggestion given to the nursing community is to be able to reach out to the existence of MSM who have a high risk of HIV AIDS and STIs. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;}
Keywords: HIV AIDS and STIs, MSM, self-care, health services